2021
DOI: 10.3389/fphys.2021.651851
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, Moderators and Reference Limits of Exercise-Induced Elevation of Cardiac Troponin T in Athletes: A Systematic Review and Meta-Analysis

Abstract: Background: Kinetics, moderators and reference limits for exercise-induced cardiac troponin T (cTnT) elevations are still unclear.Methods: A systematic review of published literature was conducted adhering to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Studies reporting high-sensitivity cardiac troponin T (hs-cTnT) concentrations before and after a bout of exercise in athletes were included and analyzed. The final dataset consisted of 62 estimates from 16 bouts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…Several studies have already shown that the kinetics of the increase are similar to those observed during a cardiac event. However, the peak is always lower and the recovery is faster ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown that the kinetics of the increase are similar to those observed during a cardiac event. However, the peak is always lower and the recovery is faster ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, cardiac troponin increases sharply after irreversible damage, which is maintained for a long time ( Park et al, 2017 ). Nevertheless, the increase in cardiac troponin induced by exercise was different in terms of hemodynamic changes ( Li et al, 2021a ; Eijsvogels et al, 2015 ; Cirer-Sastre et al, 2021 ). Most studies have shown that the decrease from the peak occurred after 3–6 h following exercise ( Park et al, 2017 ; Eijsvogels et al, 2014 ; Hosseini et al, 2018 ; Eijsvogels et al, 2015 ; Chan-Dewar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 94%
“…Overall intensity, duration, and exercise types are factors that affected the level of cardiac troponin after exercise ( Li et al, 2021a ; Takahashi & Miyamoto, 1998 ; Martínez-Navarro et al, 2020 ; Richardson et al, 2018 ). The differences were evident particularly in the comparison of exercise intensity such as between HIIE and MICE ( Weippert et al, 2016 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…All participants were required to abstain from moderate or strenuous exercise for 48 h before the post-training test. The timing for the post-exercise blood samples was based on: 1) previous studies have shown that the cTnT elevation response to exercise is transient and cTnT generally returns to baseline within 48 hours post-exercise [23,24]; and 2) this is the longest resting time between two training sessions when training is performed 4 days per week; the cTnT values obtained may be considering baseline (resting) values during the structured training period.…”
Section: Experimental Designmentioning
confidence: 99%